2016
DOI: 10.3389/fnins.2016.00589
|View full text |Cite|
|
Sign up to set email alerts
|

Recombinant hNeuritin Promotes Structural and Functional Recovery of Sciatic Nerve Injury in Rats

Abstract: Neuritin is a new neurotropic factor implicated in nervous system development and plasticity. Studies have shown that Neuritin is upregulated in injured nerves, suggesting that it is involved in nerve repair. To test this hypothesis, we investigated whether recombinant human Neuritin could restore nerve structure and function in a rat model of sciatic nerve injury. Neuritin treatment had a dose-dependent effect on functional recovery 4 weeks after injury, as determined by the walking-track test. Similar trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…A recent study supported neuroprotective effects of neuritin by reporting that adeno-associated virus (AAV)-mediated overexpression of neuritin delayed RGC apoptosis, regenerated injured axons, and maintained RGC function following ONI 41 . Similar protective effects of neuritin was reported in a rat model of sciatic nerve injury 42 .…”
Section: Discussionsupporting
confidence: 83%
“…A recent study supported neuroprotective effects of neuritin by reporting that adeno-associated virus (AAV)-mediated overexpression of neuritin delayed RGC apoptosis, regenerated injured axons, and maintained RGC function following ONI 41 . Similar protective effects of neuritin was reported in a rat model of sciatic nerve injury 42 .…”
Section: Discussionsupporting
confidence: 83%
“…Stimulating electrodes applied on proximal end to generate action potential which is measured by recording electrodes from distal end. 28 Conduction velocity is calculated by formula Here latent period is the time elapsed between the applications of stimulus until the peak of the maximum compound action potential (CAP). 29…”
Section: Motor Nerve Conduction Velocity Evaluation (Mncv)mentioning
confidence: 99%
“…Using a similar optic nerve crush model, Sharma et al evaluated the axogenic properties of neuritin on axotomized RGCs in vitro and on the optic nerve in vivo, and found that recombi-a classical marker of axonal regeneration, were observed within the optic nerves of the adeno-associated virus (AAV)2neuritin group, suggesting that neuritin preserved RGC function on axotomized RGCs in vitro and after axonal injury in vivo [30] . Using a sciatic nerve injury model in rats, Wang et al reported that recombinant human neuritin stimulated nerve regeneration and restored motor function, as assessed by the walking-track test and nerve conduction velocity; and thus promoted the repair of injured sciatic nerves [31] . Although, neuritin can be both down-regulated and up-regulated at different stages in different injury models, the overall levels of neuritin increase after nerve injury; indicating that axonal neuritin protein synthesis may provide a spatially restricted mechanism for promoting axonal growth.…”
Section: Neuritin Promotes Neuritogenesis and Neuronal Regenerationmentioning
confidence: 99%